EFEKTIVITAS PENERAPAN METODE PEMBELAJARAN TASK BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Sofiya Sofiya; Moh. Afiful Hair (Lembaga Sepercenter, 2025)
This study examines the effectiveness of the Task-Based Learning (TBL) method in improving student learning outcomes in Islamic Religious Education (PAI) at Al-Hikmah Gugul Tlanakan Pamekasan Junior High School. The research aims to assess both the effectiveness of TBL and the factors influencing its implementation. The main problems discussed are: (1) how effective TBL is in improving students’ learning outcomes, and (2) the supporting and inhibiting factors in applying this method.Using a qualitative descriptive approach, data were collected from the principal, PAI teachers, and students through observation and interviews. Data analysis involved reduction, presentation, and verification.Findings reveal that effective learning requires professional teachers who can select suitable teaching methods. The TBL method is considered quite effective in enhancing students’ understanding, motivation, and engagement in learning activities. Improved learning outcomes were evident from observations and interviews. Supporting factors include student cooperation, teacher motivation, high interest in learning, adequate learning media, and experienced teachers. Inhibiting factors involve limited student participation, low attention to teacher instructions, physical fatigue, and lack of enthusiasm in some learners.